2010
DOI: 10.1007/s11999-009-1025-1
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Femoral Nerve Block for Total Knee Arthroplasty

Abstract: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
123
1
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(138 citation statements)
references
References 22 publications
4
123
1
10
Order By: Relevance
“…Similarly, in a study of 1018 TKAs with or without a single-injection FNB, 12 patients in the FNB group fell, whereas only one patient fell in the group without a FNB. Also, eight of the 12 patients who fell had documented quadriceps weakness before their fall [17]. In our study, quadriceps strength was tested on Postoperative Day 2 for the first time after surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, in a study of 1018 TKAs with or without a single-injection FNB, 12 patients in the FNB group fell, whereas only one patient fell in the group without a FNB. Also, eight of the 12 patients who fell had documented quadriceps weakness before their fall [17]. In our study, quadriceps strength was tested on Postoperative Day 2 for the first time after surgery.…”
Section: Discussionmentioning
confidence: 94%
“…A number of studies have described complications related to nerve blocks [14,21,29]. Feibel et al [14] reported on two groups of patients undergoing TKA with both groups receiving femoral nerve blocks but with different durations.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the more common methods of pain management include peripheral nerve blocks (femoral with or without sciatic nerve block) and intraarticular/periarticular injections. The perceived advantage of peripheral nerve blocks is effective pain management; disadvantages include slower recovery of lower extremity function [9], time required for the procedure, complications related to the block [14,21,29], and added cost. Because of the limited duration of action of the local anesthetic, there is the perception that single periarticular injections may not provide good pain relief beyond the first day [20].…”
Section: Introductionmentioning
confidence: 99%
“…In a center performing 500 TKAs a year, the resources required to administer this program would be equivalent to approximately 0.1 full-time nursing position (15 to 30 minutes multiplied by 500 patients = 125 to 250 person/hours with an average work year of 2000 person/ hours). Other initiatives may also be successful at reducing falls, such as the use of an immobilizer while peripheral nerve blocks are in effect, and may be associated with lower costs [17]. In addition, it is unknown whether fall reduction education may be delivered in a group setting or by a video, which would be more cost-effective and yet maintain the proven benefits.…”
Section: Discussionmentioning
confidence: 99%
“…These postoperative falls represent a major source of potential morbidity for the patient, as well as regulatory and financial liability for the institution; therefore, substantial resources have been expended to understand which patients are at risk for falling and when these falls occur [2,4,10,12,15,16]. Numerous factors associated with falls have been identified, some of which are intrinsic to the patient, such as age and cognitive impairment, while other factors are related to the procedures and treatments that they undergo, such as medication side effects and muscle weakness from peripheral nerve blocks [3,9,10,13,17]. External factors may also play a role, including room design, bed height, and staff-to-patient ratios [19,20].…”
Section: Introductionmentioning
confidence: 99%